Peran Guru dalam Penanaman Nilai-Nilai Dasar Pancasila dengan Menggunakan Media Pembelajaran Google Classroom - Fiqi Ni'matul Hikmah; Agus Nur Sholeh; Mustajab Mustajab (IAINU Kebumen, 2022)
This study aims to describe the increase in understanding of learning outcomes in the material ofbasic values of Pancasila by using the Google classroom learning media for class V MI AlHidayah Karangtanjung during the pandemic period of the 2021/2022 school year. In this studyusing a qualitative approach. Students of class V MI Al Hidayah Karangtanjung. The researcheracts as an observer in instilling the basic values of Pancasila for the fifth grade students of MI AlHidayah Karangtanjung. The research instrument used is by using data collection techniques,observation, interviews, documentation and data analysis techniques, namely data reduction, datapresentation and verification. The results of the study found the role of the teacher in instillingthe basic values of Pancasila, which was to lead students to have an attitude of mutualcooperation, mutual respect, not mockery, the attitude of class V students who seemed to respectthe teacher, shook hands with the teacher, greeted the teacher when they met, and bowed theirheads when walking past the teacher